Features of the Structure, Development and Functioning of The Immune System of The Child’s Body - Kodirov Khusan Solievich (Genius Journals, 2024)
The development of an individual in ontogenesis occurs in accordance with its inherent genome strategy, i.e. the totality and characteristics of the implementation of genetic information, fixed by previous evolution and inherited from parents. During certain periods, events occur that turn on/off the regulatory mechanisms of certain groups of immune system genes responsible for the morphofunctional formation, unity, effector and regulatory efficiency of nonspecific and specific processes of immunological surveillance and anti-infective immunity
Keywords: Immune system; children; formation; effect